2016
DOI: 10.1039/c6py00856a
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of bioorthogonal chemistries towards site-specific polymer–protein conjugation

Abstract: Polymer conjugation to proteins has been widely used to improve or expand protein properties. However, polymer conjugation to random sites of a target protein often led to a significant loss of critical protein properties. In order to overcome this, polymer conjugation to specific sites of a protein was developed using the site-specific introduction of non-natural amino acids and bioorthogonal chemistries. This review summarizes the recent advances in bioorthogonal chemistries. As the repertoire of bioorthogon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 229 publications
(510 reference statements)
0
31
0
Order By: Relevance
“…Site-specific incorporation of a non-natural amino acid into a target protein inside host cells has been achieved by the co-expression of an orthogonal pair comprising aminoacyl-tRNA synthetase/tRNA that is specific for the non-natural amino acid ( Figure 1) [33,34]. Some non-natural amino acids in particular have "clickable" functional groups [35]. The site-specific incorporation of a clickable non-natural amino acid combined with the corresponding click chemistry enables site-specific conjugation to a target protein [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Site-specific incorporation of a non-natural amino acid into a target protein inside host cells has been achieved by the co-expression of an orthogonal pair comprising aminoacyl-tRNA synthetase/tRNA that is specific for the non-natural amino acid ( Figure 1) [33,34]. Some non-natural amino acids in particular have "clickable" functional groups [35]. The site-specific incorporation of a clickable non-natural amino acid combined with the corresponding click chemistry enables site-specific conjugation to a target protein [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The highly nucleophilic sulfhydryl side chain group within cysteines can undergo alkylation with maleimides or iodoacetamides. In addition, they can be reacted with disulfide-containing reagents via exchange procedure ( Jung and Kwon, 2016 ). Unfortunately, it is often challenging to target cysteine residues, as they are among the rarest residues, usually involved in disulfide bonds or buried in hydrophobic pockets.…”
Section: Strategies For the Fabrication Of Enzyme-polymer Hybridsmentioning
confidence: 99%
“…For those experiments in which a high degree of control of the hybrid is a must, in terms of both the grafting density and the precise localization of the chains on the surface of the enzyme, highly efficient bioorthogonal chemistries are applied. Successful stories of site-selective bioconjugation have been achieved using thiol-ene ( Jung and Kwon, 2016 ), alkyne-azide ( Boyer et al, 2009 ), Diels-Alder ( Sun et al, 2008 ) or Staudinger ( Serwa et al, 2010 ) “click” reactions. The bioorthogonal reactions can be performed in presence of many nucleophiles, electrophiles, reductants, oxidants, or water without altering or affecting the evolution of the reaction, because they are not present in biological systems.…”
Section: Strategies For the Fabrication Of Enzyme-polymer Hybridsmentioning
confidence: 99%
“…Numerous studies have reported on immobilization and functionalization (such as PEG‐ylation, dendrylation etc.) of proteins using click chemistry or similar bioorthogonal handles incorporated in translated proteins . These studies usually aim at production of specifically modified proteins which are normally of general biotechnological interest; however, the adaptation of these chemical means may in principle become a source of new‐to‐nature motifs.…”
Section: “Entry Points” For Ncaas In the Experimental Attempts To Engmentioning
confidence: 99%